Ecology of Cyprinus carpio var. specularis (Physico-Chemical Conditions of the Habitat) (Journal of Science Foundation, 2013)
The study was carried out from November 2010 to August 2011. The study was conducted on the Atrai river, a flood plain and a culturable pond of Naogaon district for the find out of ecology of Cyprinus carpio var. specularis. The mean values of air temperature of Atrai river, flood plain and pond was 28.17. The mean values of water temperature of Atrai river, flood plain and pond was 26.39, 26.61 and 25.81°C, respectively. The mean values of water transparency of Atrai river, flood plain and pond was 57.25, 47.20 and 41.32cm, respectively. The mean values of rainfall of Atrai river, flood plain and pond was 121.19. The mean values of pH of Atrai river, flood plain and pond was 8.03, 7.91 and 7.73, respectively. The mean values of DO of Atrai river, flood plain and pond was 5.99, 6.43 and 5.93 mg/l, respectively. The mean values of CO2 of Atrai river, flood plain and pond was 6.87, 6.87 and 6.77 mg/l, respectively. DOI: http://dx.doi.org/10.3329/jsf.v9i1-2.14656 J. Sci. Foundation, 9(1&2): 133-139, June-December 2011